Beyond depression: examining the role of anxiety and anxiety sensitivity on subjective cognition and functioning in older adults. (28th October 2022) - Divers, Ross; Robinson, Anthony; Miller, Luke; De Vito, Alyssa N.; Pugh, Erika; Calamia, Matthew
Abstract: Objectives: Subjective cognitive difficulties in the elderly may serve as potential risk-factors for future, objective decline and conversion to neurodegenerative disorders (e.g., mild cognitive impairment [MCI] and dementia). Though these subjective declines have been associated with depression, and to a lesser extent, anxiety, it is unknown if related constructs (e.g. anxiety sensitivity) and specific kinds of worries (e.g. worry about developing dementia, health anxiety) are related to subjective declines. The current study sought to examine if cognitive concerns related to anxiety sensitivity, dementia worry, and health anxiety added incremental validity beyond general symptoms of anxiety and depression in predicting subjective cognition and functioning in a sample of older adults. Methods: Participants were 429 older adults who were at least 60 years old. Participants completed questionnaires on subjective cognition, subjective everyday function, anxiety, depression, anxiety sensitivity, dementia worry, and health anxiety via Qualtrics Panels. Hierarchical multiple regressions were conducted. Results: Our variables of interest (anxiety sensitivity, dementia worry, and health anxiety) added significant variance in predicting subjective cognition and everyday function. Specifically, anxiety sensitivity was related to subjective cognition and functioning, while dementia worry and health anxiety were variably associated. Conclusion: Our results suggest that constructs related to anxiety and worry have a significant relationship with subjective cognition and function in older adults beyond general symptoms of depression and anxiety. Future work should examine if interventions and education may help to decrease anxiety sensitivity and worry about dementia respectively in older adults, which may in tern protect against future subjective declines.